PENGARUH PEMAHAMAN SISTEM ADMINISTRASI PAJAK DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK DALAM MELAPORKAN SPT TAHUNAN DENGAN TINGKAT KEPUASAN WAJIB PAJAK PADA FORMULIR 1721-A2 SEBAGAI VARIABEL INTERVENING: (STUDI KASUS KABUPATEN BOYOLALI) - Ardila Setyowati; Maya Widyana Dewi; Darmanto Darmanto (Jurnal Ilmiah Akuntansi, 2024)
This paper aims to find out the effect of Understanding Tax Administration and Fiscus Services onTaxpayer Compliance through Taxpayer Satisfaction on Form 1721-A2 as an Intervening Variable. The population in this study was Taxpayers on Form 1721-A2 at KPP Pratama Boyolali with a total of 100 taxpayers responding. The sampling technique uses non-probability sampling. This type of research is quantitative research. Data was obtained directly through distributing questionnaires at KPP Pratama Boyolali as well as by distributing via gform. Data analysis uses Path Analysis (multiple regression model and mediation model). The research results show 1) Understanding Tax Administration and Fiscus Services has a positive and significant effect to Satisfaction, 2) Understanding Tax Administration and Fiscus Services has a positive and significant effect to Compliance, 3) Satisfaction cannot mediate between Understanding Tax Administration and Fiscus Services has a positive and significant effect towards Compliance.